Research advances on the role of microinflammatory state in vascular calcification in chronic kidney disease - Yu Ping; Zou Chun-bo (Linchuang shenzangbing zazhi)
The annual incidence of chronic kidney disease （CKD） is rising rapidly in China. It causes a high economic burden on health system. Vascular calcification （VC） is one of the major causes of cardiovascular adverse events in CKD patients. The formation mechanism of VC has not been completely elucidated. Microinflammatory state is closely correlated with the formation of VC. The activation of monocyte phagocyte system， the releases of tumor necrosis factor α， interleukin， C-reactive protein and ratio of inflammatory parameters may participate in the occurrence and development of VC.